Who's Managing Otolaryngologic Conditions in the United States?. (4th July 2017) - Sun, Gordon H.; Cain‐Nielsen, Anne; Moloci, Nicholas M.
Abstract : Growth of an aging US population, coupled with implementation of the Patient Protection and Affordable Care Act, will pose logistical challenges for the primary care provider (PCP) workforce for the foreseeable future. In particular, the burden of otolaryngologic care placed on PCPs is substantial, based on research dating back to the 1970s and confirmed by a recent analysis of the US National Ambulatory Medical Care Survey. Collaboration between the otolaryngology and primary care communities will be needed to ensure that PCPs gain adequate exposure and training in routine otolaryngology care to improve the clinical management of ear, nose, and throat conditions in an expanding population.